A study of quit smoking achievement and predictors after six months quit smoking program at Putrajaya Hospital / Nurhazira Alang - Alang, Nurhazira (2016)
Background: Smoking cigarette leads to health related morbidity and mortality. Therefore, a lot of campaign and policies had been carried out in Malaysia to achieve the quit smoking rate. Objectives: The aims of the study were to determine the demographical distribution of smokers, choice of treatment and the adverse events, which is to identify the predictors of smoking cessation. Methodology: This is a retrospective study by examining the records of all of the smokers who attended the quit cessation clinic in Putrajaya Hospital. Data were extracted from electronic system namely THIS and manual form carried out from 1 January 2014 to December 2014. Results: A total of 58 patients met the inclusion criteria, 34 (58.62%) were quitters during the follow up while 24 (41.38%) did not quit. The mean age was 38.79±11.79 and all of the patients were male. The mean number of cigarettes smoked per day was 17±9 cigarettes per day. 93% (54) patients used varenicline as their treatment. Of these, 59.36% were successful in quitting and 33.33% reported having nausea. The median of the carbon monoxide level (CO) before and after the program for quitters and smokers are significantly different (p<0.05). In univariate analysis, hypertension disease (OR 0.15, 95% CI: 0.03-0.81) and heart disease (OR 0.19, 95% CI: 0.03-1.03) were less likely to quit smoking. Univariate and multivariate analysis presented that, those who were quitted because of family or friends were more likely successful in quitting (OR 5.53, 95% CI: 1.38-22.10, OR 8.13, 95% CI: 1.53-43.34). Conclusion: Varenicline is the first choice of treatment and the highest adverse effects is nausea. CO level is a better indicator in identifying the smoking status. The strongest predictors of quitting smoking were influence by family members or friends.